Atendimento Educacional Especializado para alunos com deficiência intelectual baseado no coensino em dois municípios - Lago, Danúsia Cardoso (2014)
The Co-teaching/Collaborative Teaching has been considered by many researchers as one of the modalities to support school inclusion service, having effective strategies for children with special needs of Special Education students - PAEE in public schools. This is one of the collaboration models in which teachers of special and regular education work in an egalitarian relationship searching for strategies to encourage enrollment of PAEE students within the regular school classroom. In this perspective, the present study aimed to develop, implement and evaluate a Specialized Educational Service Program - AEE based on Co-teaching, for students with intellectual disabilities in the regular classroom context at four public schools of two cities. The study was conducted in four public schools of two cities: São Carlos - São Paulo in 2011 and Vitória da Conquista - Bahia in 2012. In this study, altogether participated the researcher, as a special education teacher; four teachers of regular classrooms and five students with intellectual disability ID. The instruments used were: a questionnaire for mapping school networks and school units; identification questionnaire and Semistructured interview script for participating teachers; Anamnese Sheet, Four Words and one Sentence Test, educational evaluations and activities for students with ID; Observation script and Field diaries with the researcher records and Rating Scale for Outer Observers - EAOE. Student data were individually analyzed qualitatively and quantitatively, considering the process analysis; teachers interviews were subjected to content analysis. The results indicated the importance of Co-teaching for participating teachers, particularly in the expansion of knowledge about ways of acting in the regular classroom with ID students; expansion of professional knowledge about managing the classroom for the special education teacher and, in the ID students there was progress in the social aspect - changes in behavior and in academic development - willingness to participate in educational activities, which supports this strategy as another model that may increase the participation of ID students in the regular school context, and provide continuing education for professionals involved. However, the support service based on Co-teaching needs to be implemented in other school systems to evaluate the generalizability of its effectiveness, so that it can influence public education policy that supports other models of AEE that can be realized in other areas, besides Multifunction Features Room - MFR.